COVID-19 and Liquidity Dynamics: Analyzing ASEAN-6 Stock Markets During and Post-Pandemic - Chi Pham Thi Bich; Linh Nguyen Ha; Thu Vu Thi Minh (SAGE Open)
This study investigates liquidity trends in key Southeast Asian markets, specifically focusing on the ASEAN-6 countries (Indonesia, Thailand, Singapore, Malaysia, Vietnam, and the Philippines) during and after the COVID-19 pandemic. Utilizing regression models, we analyze how trading volume, volatility, price movements, and their interactions have collectively influenced liquidity dynamics across these markets within 121 days around the pandemic’s announcement. We use three primary liquidity indicators: bid-ask spreads, Amihud’s illiquidity ratio, and the return-turnover ratio. The findings indicate that in the short term, COVID-19 shock, trading volume, and volatility significantly affected liquidity across the ASEAN-6 indices, with notable variations among the markets. Specifically, the Singapore and Malaysia markets demonstrated a greater capacity to absorb and adapt to pandemic-induced disruptions, showing the least decline and a swift recovery within 121 days around the pandemic’s announcement. Furthermore, our descriptive analysis highlights that Indonesia, Singapore, and Malaysia (KLSE) have emerged as the top-performing markets in terms of liquidity throughout the pandemic and its aftermath.